2020
DOI: 10.1371/journal.pone.0235015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of azaspiracid-producing dinophyte species and their toxins in North Atlantic and North Sea waters in summer 2018

Abstract: Representatives of the marine dinophyte family Amphidomataceae produce lipophilic phycotoxins called azaspiracids (AZA) which may cause azaspiracid shellfish poisoning (AZP) in humans after consumption of contaminated seafood. Three of the four known toxigenic species are observed frequently in the eastern North Atlantic. In 2018, a research survey was performed to strengthen knowledge on the distribution and abundance of toxigenic Amphidomataceae and their respective toxins in Irish coastal waters and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 69 publications
(104 reference statements)
0
24
0
Order By: Relevance
“…spinosum and Am. languida and thereby have added complementary information to the field data set on the abundance and distribution of toxigenic Amphidomataceae and their toxins to that which have been published previously [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…spinosum and Am. languida and thereby have added complementary information to the field data set on the abundance and distribution of toxigenic Amphidomataceae and their toxins to that which have been published previously [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Azadinium spinosum , the first identified source organism of AZA, is regarded as the most important AZA producer in Irish waters [ 18 , 25 , 34 ]. The first strains of this species isolated from Scotland [ 21 ], Denmark [ 52 ], the Shetland Islands [ 24 ], and Ireland [ 18 ] all share the same sequence data and toxin profile consisting of AZA-1, AZA-2, and AZA-33, but subsequent multiple strain studies from Norway and Argentina revealed ribotype divergence and toxin profile diversity within Az.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations